A novel de novo TBX5 mutation in a patient with Holt-Oram syndrome - Ríos-Serna LJ; Díaz-Ordoñez L; Candelo E; Pachajoa H (The Application of Clinical Genetics, 2018)
Lady J Ríos-Serna,1 Lorena Díaz-Ordoñez,1 Estephania Candelo,1,2 Harry Pachajoa1,3 1Center for Research on Congenital Anomalies and Rare Diseases (CIACER), Department of Basic Medical Sciences, Universidad Icesi, Cali, Valle del Cauca, Colombia; 2Biomaterial and Tissues Engineering and Genetic of Human Diseases, University College London, London, UK; 3Fundación Valle del Lili, Cali, Valle del Cauca, Colombia Abstract: Holt-Oram syndrome (HOS) is an autosomal dominant disorder characterized by congenital cardiac defects and congenital deformities of the upper limbs. Herein, we report the case of a 2-year-old patient presenting with clinical diagnostic criteria of HOS with interatrial and interventricular communication associated with hip dysplasia and upper limb reduction composed of radial ray anomaly. A novel de novo, potentially pathogenic variant in the TBX5 gene at NM_181486.2:c.243-1G>C was identified. Keywords: Holt-Oram syndrome, heart-hand syndrome, de novo mutation, TBX5.i>